Influence of bed age and flocculation dynamics on turbidity current propagation - Wahab, S. A.; Chassagne, C.; Helmons, R. L. J. (Frontiers in Earth Science, 2026)
In this study, the influence of a bed on turbidity current propagation and flocculation dynamics has been investigated using a lock-exchange setup. Experiments were performed in saltwater using sediments sampled from a deep-sea mining location in the Clarion Clipperton Zone (CCZ). Results showed that the presence of a bed influenced the propagation velocity of turbidity currents. Flocs were denser and larger than those observed when no bed was present. The floc settling velocities also increased in the presence of a bed. Additionally, in the case of a (freshly) formed bed, sediment resuspension occurred due to the disturbance of organic matter, which contributed to flocculation. This study also sheds light on the role of the age of the bed on turbidity current propagation, with (freshly) formed beds being efficient in reducing sediment spread. These findings are important for predicting the spread of a turbidity current during deep-sea mining activities.